Total shoulder arthroplasty after previous arthroscopic surgery for glenohumeral osteoarthritis: a case-control matched cohort study - Nolte, Philip-Christian; Elrick, Bryant P.; Arner, Justin W.; Ridley, T.J.; Woolson, Thomas E.; Nolte, Anna-Katharina; Midtgaard, Kaare S.; Millett, Peter J. (The American journal of sports medicine, 2021)
Background:When comprehensive arthroscopic management (CAM) for glenohumeral osteoarthritis fails, total shoulder arthroplasty (TSA) may be needed, and it remains unknown whether previous CAM adversely affects outcomes after subsequent TSA.Purpose:To compare the outcomes of patients with glenohumeral osteoarthritis who underwent TSA as a primary procedure with those who underwent TSA after CAM (CAM-TSA).Study Design:Cohort study; Level of evidence, 3.Methods:Patients younger than 70 years who underwent primary TSA or CAM-TSA and were at least 2 years postoperative were included. A total of 21 patients who underwent CAM-TSA were matched to 42 patients who underwent primary TSA by age, sex, and grade of osteoarthritis. Intraoperative blood loss and surgical time were assessed. Patient-reported outcome (PRO) scores were collected preoperatively and at final follow-up including the American Shoulder and Elbow Surgeons (ASES) score, Single Assessment Numeric Evaluation (SANE), shortened version of Disabilities of the Arm, Shoulder and Hand (QuickDASH), 12-Item Short Form Health Survey Physical Component Summary (SF-12 PCS), visual analog scale, and patient satisfaction. Revision arthroplasty was defined as failure.Results:Of 63 patients, 56 of them (19 CAM-TSA and 37 primary TSA; 88.9%) were available for follow-up. There were 16 female (28.6%) and 40 male (71.4%) patients with a mean age of 57.8 years (range, 38.8-66.7 years). There were no significant differences in intraoperative blood loss (P > .999) or surgical time (P = .127) between the groups. There were 4 patients (7.1%) who had failure, and failure rates did not differ significantly between the CAM-TSA (5.3%; n = 1) and primary TSA (8.1%; n = 3) groups (P > .999). Additionally, 2 patients underwent revision arthroplasty because of trauma. A total of 50 patients who did not experience failure (17 CAM-TSA and 33 primary TSA) completed PRO measures at a mean follow-up of 4.8 years (range, 2.0-11.5 years), with no significant difference between the CAM-TSA (4.4 years [range, 2.1-10.5 years]) and primary TSA (5.0 years [range, 2.0-11.5 years]) groups (P = .164). Both groups improved significantly from preoperatively to postoperatively in all PRO scores (P < .05). No significant differences in any median PRO scores between the CAM-TSA and primary TSA groups, respectively, were seen at final follow-up: ASES: 89.9 (interquartile range [IQR], 74.9-96.6) versus 94.1 (IQR, 74.9-98.3) (P = .545); SANE: 84.0 (IQR, 74.0-94.0) versus 91.5 (IQR, 75.3-99.0) (P = .246); QuickDASH: 9.0 (IQR, 3.4-27.3) versus 9.0 (IQR, 5.1-18.1) (P = .921); SF-12 PCS: 53.8 (IQR, 50.1-57.1) versus 49.3 (IQR, 41.2-56.5) (P = .065); and patient satisfaction: 9.5 (IQR, 7.3-10.0) versus 9.0 (IQR, 5.3-10.0) (P = .308).Conclusion:Patients with severe glenohumeral osteoarthritis who failed previous CAM benefited similarly from TSA compared with patients who opted directly for TSA.
Gesehen am 05.08.2021